2000
DOI: 10.1046/j.1365-2826.2000.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pars Tuberalis: The Missing Link in the Photoperiodic Regulation of Prolactin Secretion?

Abstract: The endocrine function of the pars tuberalis of the pituitary gland has been an enigma for many years. Recent work suggests that one of its primary functions in seasonal mammals is to mediate photoperiodically regulated changes in prolactin secretion via an unidentified factor called tuberalin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 99 publications
1
83
0
Order By: Relevance
“…Subsequently, the PT has been adopted as a model system to investigate the molecular mechanisms involved in decoding melatonin signal duration and long-term timing (Morgan 2000, Hazlerigg et al 2001. This rests on the ability to readily manipulate PT cells in vitro using primary cell cultures from animals set up on specific photoperiods, and the ability to study the long-term PT-control of prolactin secretion in vivo using hypothalamo-pituitary disconnected (HPD) sheep where the complications of direct inputs from the hypothalamus are removed (see below).…”
Section: Decoding the Melatonin Signal In The Pt Calendar Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the PT has been adopted as a model system to investigate the molecular mechanisms involved in decoding melatonin signal duration and long-term timing (Morgan 2000, Hazlerigg et al 2001. This rests on the ability to readily manipulate PT cells in vitro using primary cell cultures from animals set up on specific photoperiods, and the ability to study the long-term PT-control of prolactin secretion in vivo using hypothalamo-pituitary disconnected (HPD) sheep where the complications of direct inputs from the hypothalamus are removed (see below).…”
Section: Decoding the Melatonin Signal In The Pt Calendar Cellmentioning
confidence: 99%
“…Comprehensive in vivo studies in HPD sheep provide further evidence that there is an interval timer and/or circannual rhythm generator within the PT (Lincoln & Clarke 1994, 1997, 2000. In the HPD animal, the pituitary gland is physically isolated from the hypothalamus by the surgical removal of the arcuate nucleus and destruction of the median eminence (Clarke et al 1983, Lincoln et al 2001.…”
Section: Interval Timer/circannual Rhythm Generator In the Pt Calendamentioning
confidence: 99%
“…This phenomenon is especially evident in seasonally breeding species. In sheep, the short day photoperiod, elevates plasma melatonin concentration which in turn leads to the inhibition in the secretion of PRL (Misztal et al, 1997;Morgan, 2000;Molik et al, 2007;Gomez-Brunet et al, 2008;Morgan and Hazlerigg, 2008;. Numerous data indicated that prolonged treatment with melatonin (i.e.…”
Section: Factors Inhibiting Prolactin Secretionmentioning
confidence: 99%
“…This supports the view that the suppression of prolactin secretion followed by a partial recovery (partial refractoriness) is a normal response to a short-day melatonin signal and that this is due to the action of melatonin in the pituitary gland. Indeed, it has been shown that melatonin inhibits PRL, acting within the pars tuberalis (PT) of the pituitary gland and that a protein factor called tuberalin, which governs both the synthesis and release of prolactin, participates in this mechanism (Morgan, 2000). A long-duration melatonin signal from short days, or a continuous melatonin signal from a melatonin implant, may suppress prolactin secretion by inhibiting the release of tuberalin from the PT.…”
Section: Factors Inhibiting Prolactin Secretionmentioning
confidence: 99%
“…Binding sites and transcripts for MT1 receptors are detected in the pre-mammillary hypothalamus, the site of melatonin action to control reproduction in sheep [14], but whether MT1 mediates the effects of melatonin on reproductive activity has yet to be determined. In contrast, the MT1 receptor expressed in the pars tuberalis (PT) of the pituitary, has been shown to mediate the effect of melatonin on seasonal changes in prolactin secretion [15][16][17]. In addition, in the PT, the number of binding sites has been shown to be significantly higher in -/-ewes when compared to +/+ ewes [12] using the radioligand 2-[ 125 I]-iodomelatonin.…”
Section: Introductionmentioning
confidence: 99%